Cleantech innovation implementation towards the sustainable development of Vietnamese Enterprises: Current situation and recommendations - Tran, Thi Kim Anh; Hoang, Truong Giang; Tran, Hoang Long (Journal of International Economics and Management, 2014)
After decades of economic growth, partly at the expense of the environment, Vietnamese government is devoting closer attention to green solutions, among which Cleantech Innovation is emerging as a significant element. This paper aims to describe the general picture of the global Cleantech industry and illustrate the essential role of Cleantech Innovation in pursuing the sustainable development goals of Vietnamese government and enterprises. The paper suggests that Cleantech Innovation is an inevitable trend towards sustainable development and thus should be further promoted in Vietnam.